Pengaruh Terapi Aktivitas Kelompok Sosialisasi (Taks) Terhadap Kemampuan Bersosialisasi dan Interaksi Sosial pada Pasien Gangguan Jiwa dengan Isolasi Sosial di Pondok 99 Kemlagi Mojokerto - Alvia Putri Mukharomatin; Ilham Akbar Maulana; Nadia Ayu Salsabila; Siti Sholikah; Abdul Rokhman (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
In people with mental disorders, the humanistic function is disrupted, so they don't want to relate and talk to other people. Decreased social skills make a person unable to interact effectively and unable to express negative or positive feelings. The purpose of this study was to analyze the effect of socialization group activity therapy on social skills and social interactions in patients with mental disorders. The research design used the Pre-Experimental One Group Pre-test-Post test which was conducted on 33 people with mental disorders who were taken using a total sampling technique. The intervention provided was in the form of socialization group activity therapy (TAKS). The research data was taken using socialization and social interaction observation sheets, then analyzed using the Wilcoxon test. Based on the results of research on social skills before being given TAKS most (69.7%) were in the poor category, after being given TAKS most (66.7%) were in the good category. The results of research on social interaction skills before being given TAKS were mostly (75.8%) in the poor category, while after being given TAKS most (69.7%) were in the good category. The results of the Wilcoxon test (p=0.000) showed that there was an effect on social skills and social interaction after being given socialization group activity therapy. Socialization Group Activity Therapy can improve a person's social skills and social interaction because this therapy is carried out in stages which are divided into five sessions so that it can make the patient open up to other people.